The risk of COVID-19 in IBD patients is increased by urban living and is not influenced by disease activity or intravenous biologics - Lelong, Margaux; Josien, Régis; Coste-Burel, Marianne; Rimbert, Marie; Bressollette-Bodin, Céline; Nancey, Stéphane; Bouguen, Guillaume; Allez, Matthieu; Serrero, Mélanie; Caillo, Ludovic; Rouillon, Cléa; Blanc, Pierre; et al. (Frontiers in Immunology, 2023)
Background: Patients with inflammatory bowel disease (IBD) may have a modified immune response to SARS-CoV-2. The objectives were to evaluate the prevalence of COVID-19 in patients treated with infliximab or vedolizumab, to analyze the factors associated with the infection, the impact of treatments and trough levels.Methods: Patients with IBD treated with intravenous biologics in 14 French centers were included between March and June 2020 and followed-up for 6 months. Blood samples were collected for serologies and trough levels. The analysis of factors associated with COVID-19 was conducted in a matched 1:1 case-control sub-study with positive patients.In total, 1026 patients were included (74.9% infliximab). Over the follow-up period, 420 patients reported the occurrence of COVID-19 symptoms; 342 had been tested of whom 18 were positive. At the end of follow-up, 38 patients had a positive serology. Considering both nasal tests and serologies together, 46 patients (4.5%) had been infected. The risk of COVID-19 was related neither to the use of treatments (whatever the trough levels) nor to disease activity. Infections were more frequent when using public transport or living in flats in urban areas.The prevalence rate of COVID-19 in this IBD population treated with intravenous infliximab or vedolizumab was the same as the one in the French population before the start of the vaccination campaign. The risk was increased by urban living and was not influenced by disease activity or biologics. Sanitary barrier measures remain the best way to protect against SARS-CoV-2 in patients with IBD in biological therapy.